Flaming dormant alfalfa for pest control - Moyer, Joseph L.; Whitworth, R. Jeffery; Davis, Holly N. (My University, 2014)
Alfalfa (Medicago sativa Leyss) is an important forage crop whose production is hampered by pests, including the alfalfa weevil (Hypera postica Gyllenhal) which is a major problem in many areas. Flaming during dormancy could be an alternative control measure. Late fall and early spring flaming at three intensities were compared with pesticide and no treatment for their effects on alfalfa weevil damage and weed density. In four site-years, flaming at high intensity generally reduced weevil damage to alfalfa. When winter annual broadleaf weeds were prevalent, flaming decreased their density. When fall and spring flaming effects were different, spring flaming gave better results.
Keywords: Weevil; Hypera; Weed control; Burning